Preparation and characterization of hard carbon from biomass for potentials application in metal-ion energy storage systems - Gonzalez Baño, Nathaly Jemina (2026)
The need for sustainable energy storage technologies has sparked interest in sodium-ion batteries (SIBs) due to the abundance and low cost of sodium. Likewise, the use of hard carbon is due to its unique properties, such as graphitic domains, a slight increase in in-terplanar spacing, and the presence of holes, compared to traditional graphite. In this study, hard carbon was synthesized from rice husk biomass at various carbonization temperatures (700°C-1100°C) and exposure times (1-2 hours), and the effect of sodium salt intercalation (NaCl, NaNO3, Na2SO4) on material performance was investigated. The hardcarbon characterization was performed using FTIR, XRD, TGA, BET, Raman, and XPS techniques. Demonstrating that increasing the carbonization temperature enhances structural rearrangement and thermal stability while reducing porosity. The sample treated at 1100°C for 2 hours exhibited the highest structural ordering and the most favorable electrochemical properties. These findings demonstrate that hard carbon derived from rice husk possesses strong potential as an anode material for sodium-ion batteries.